Educators, Copyright and Open Education Resources in Massive Open Online Courses - Czerniewicz, Laura; Deacon, Andrew; Walji, Sukain (Proceedings of the International Conference on Networked Learning, 2018)
This study explored how educators, in an enabling open environment, understand and express copyright, licences, and the legal dimensions of openness as they moved from a traditional teaching role to creating massive open online courses (MOOCs). The MOOCs were produced in partnership with the Centre for Innovation in Learning and Teaching (CILT) at the University of Cape Town (UCT). CILT has a long-standing engagement with an enabling open environment and support for OER and the university has an open access policy. Nevertheless, it could not be assumed that the educators making the MOOCs had a commitment to or knowledge of open education resources (OERs), nor could it be assumed that they were interested in or had expertise in copyright, particularly as pertaining to MOOCs. While there are several other open practices relevant to making MOOCs, this paper focuses on the legal aspects, on educator engagement with OER content that has used legal mechanisms for sharing. Legal openness draws on understanding and engaging with copyright; using legally open content; making content legally open in different ways; open licensing expertise and advice (Hodgkinson-Williams, 2014). It is premised on an understanding of the legal mechanisms required to adopt (including both creation and use) such content, and therefore within the ambit of copyright management. Thus an understanding alternative forms of licensing means a priori an engagement with copyright.